THE EFFECT OF WORK-LIFE BALANCE ON EMPLOYEE PERFORMANCE: CASE STUDY AT PT. KAMIIDEA INDONESIA - Ardhia Cahyani; Putri Oktaviana; Agung Surya Dwianto (LP2M Universitas Bina Bangsa, 2024)
This research explores the influence of work-life balance on employee performance at PT. Kamiidea Indonesia. Using a qualitative approach with a case study design, this research involved in-depth interviews with employees, participant observation, and document analysis. The research results show that work-life balance has a significant positive correlation with employee performance. Employees who feel they have a good balance between their personal and work lives report higher levels of job satisfaction, motivation, and organizational commitment. Additionally, they also show lower stress levels and better productivity. These findings support previous literature linking work-life balance with various aspects of employee performance. Furthermore, this study identified several mechanisms underlying the relationship between work-life balance and performance. Work-life balance Good ones can increase employees' psychological energy, so they have a greater capacity to engage in work and achieve organizational goals. Besides that, work-life balance can also increase perceptions of organizational justice, which in turn can increase employee commitment. These findings provide an important empirical contribution to a more comprehensive understanding of the relationship between work-life balance and employee performance in the context of companies that implement work flexibility policies